Nanometer composite precise ceramic injection molding material and preparation method thereof

By adopting nanocomposite precision ceramic injection molding formula and intelligent preparation process in ceramic injection molding materials, the problems of deformation and shrinkage of traditional ceramic injection molding materials during the sintering process are solved, and higher mechanical properties and thermal stability are achieved.

CN119350006AInactive Publication Date: 2025-01-24苏州芯合半导体材料有限公司

Patent Information

Application Number
CN202411334825.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional ceramic injection molding often suffers from deformation and shrinkage during high-temperature sintering, which affects product accuracy and performance.

Method used

Using nano-composite precision ceramic injection, its formula includes aluminum oxide powder, nano-oxidation, graphene, carbon nanotubes and other components. Intelligent preparation technology, control the deformation and contraction during sintering.

Benefits of technology

It significantly reduces the deformation and contraction during sintering, improves mechanical properties and thermal stability, and ensures the density and uniformity of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057982410000081
    Figure BDA0005057982410000081
  • Figure BDA0005057982410000091
    Figure BDA0005057982410000091
Patent Text Reader

Abstract

The invention discloses a nano composite precise ceramic injection molding material and a preparation method thereof, and belongs to the technical field of semiconductor packaging. The nano composite precision ceramic injection molding material is prepared from the following components: aluminum oxide powder, nano zirconium oxide, graphene, carbon nanotubes, an organic binder, a dispersing agent and a lubricating agent, the aluminum oxide powder is composed of aluminum oxide powder with three particle sizes. According to the ceramic injection molding material, through gradient particle size distribution, a nano reinforcing system, organic system optimization and a dispersion-lubrication synergistic effect, deformation and shrinkage in the sintering process are effectively controlled, and meanwhile, the mechanical property and the thermal stability are also improved. And the adopted intelligent preparation process ensures that the compactness and the uniformity are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor packaging, and in particular to a nano-composite precision ceramic injection molding material and a preparation method thereof. Background Art

[0002] In the field of semiconductor packaging, the performance of ceramic injection molding is crucial to product quality. The basic process flow of ceramic injection molding mainly includes four stages: feed preparation, injection molding, degreasing and sintering. First, the ceramic powder is mixed with the binder to form a uniform feed; then the mixture is injected into the mold through the injection molding machine, and after the degreasing and sintering steps, a densified ceramic blank is finally obtained. This process can achieve highly precise dimensional control and complex shape manufacturing, while traditional ceramic injection molding often has problems such as deformation and shrinkage during high-temperature sintering, affecting product accuracy and performance.

[0003] Therefore, there is an urgent need to provide a new ceramic injection molding material and a preparation method thereof, wherein the ceramic injection molding material prepared by the preparation method can significantly improve problems such as deformation and shrinkage. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a nanocomposite precision ceramic injection molding material and a preparation method thereof, which effectively controls deformation and shrinkage during sintering through gradient particle size distribution, nano-enhanced system, organic system optimization and dispersion-lubrication synergy, while also improving mechanical properties and thermal stability. The intelligent preparation process adopted ensures its improvement in density and uniformity.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] The first aspect of the present invention provides a nano-composite precision ceramic injection molding material, comprising the following components in weight percentage: 65-70% alumina powder, 5-8% nano zirconium oxide, 0.3-0.5% graphene, 0.2-0.4% carbon nanotubes, 20-25% organic binder, 1-2% dispersant, and 0.5-1% lubricant; the alumina powder is composed of alumina powder of three particle sizes.

[0007] Furthermore, the three types of alumina powders are composed of 0.5 μm (D50) alumina powder, 1 μm (D50) alumina powder and 2 μm (D50) alumina powder in a mass ratio of (5-6): (4-5): (3-4). Furthermore, the organic binder is composed of polyethylene, polypropylene and paraffin in a mass ratio of (5-6): (4-5): (1-1.5).

[0008] Furthermore, the organic binder is composed of polyethylene, polypropylene and paraffin in a mass ratio of (5-6):(4-5):(1-1.5).

[0009] Furthermore, the dispersant consists of oleic acid and polyethylene glycol in a mass ratio of 1:1.

[0010] Furthermore, the lubricant is composed of stearic acid and zinc stearate in a mass ratio of (3-5):(2-5).

[0011] A second aspect of the present invention provides a method for preparing a nanocomposite precision ceramic injection molding material, comprising the following steps:

[0012] (1) Alumina powder pretreatment: Alumina powders of three particle sizes are dried and graded. 尹凡华

[0013] (2) Dispersion of nanomaterials: Add nano zirconium oxide, graphene and carbon nanotubes to anhydrous ethanol in the proportions described in claim 1, perform ultrasonic dispersion treatment, and then dry; Ultrasonic dispersion treatment is used to ensure that nano zirconium oxide, graphene and carbon nanotubes are evenly dispersed and avoid agglomeration, thereby laying a foundation for subsequent uniform mixing and performance improvement.

[0014] (3) Powder mixing: The powders of step (1) and step (2) are placed in a ball mill for ball milling to obtain mixed powders. The high-energy ball milling technology is used to achieve uniform mixing of micron-scale alumina powder and nano-scale reinforcement phase, thereby promoting the formation of a multi-scale composite structure.

[0015] (4) Mixing: The organic binder is heated until it is melted, and the powder mixed in step (3) and the melted organic binder are added to a mixing device, and then a dispersant and a lubricant are added, and vacuum mixing is performed.

[0016] (5) Intelligent granulation: Use intelligent granulation equipment with an online particle size analyzer, extrusion temperature 100-120°C, screw speed 20-40rpm, cutting speed automatically adjusted according to real-time particle size distribution, target particle size 2-5mm, cooling temperature 15-20°C. Real-time particle size analysis and automatic adjustment ensure uniform particle size after granulation, which improves the uniformity and stability of subsequent injection molding.

[0017] (6) Injection molding: Use intelligent injection molding equipment equipped with cavity pressure sensor and temperature sensor, barrel temperature: 85-95℃ in feeding section, 100-110℃ in compression section, 110-130℃ in metering section; mold temperature 35-45℃, injection pressure 70-90MPa, injection speed is adjusted in real time according to cavity pressure to ensure uniform filling, holding time 10-20 seconds, holding pressure 50-70MPa.

[0018] Preferably, the barrel temperature is set as follows: 90°C in the feeding section, 105°C in the compression section, and 120°C in the metering section. The mold temperature is 40°C and the injection pressure is 80MPa. The injection speed is adjusted in real time according to the cavity pressure to ensure uniform filling. The holding time is 15 seconds and the holding pressure is 60MPa. The three-stage temperature control of the barrel during injection molding (90°C, 105°C, 120°C) ensures the optimal fluidity of the material, reduces the generation of internal stress, and thus reduces the risk of deformation in subsequent processing. The optimized pressure control during the injection molding process (injection pressure 80MPa, holding pressure 60MPa) not only ensures the integrity of the filling, but also avoids residual stress caused by excessive pressure, which is crucial to reducing subsequent deformation.

[0019] (7) Intelligent degreasing: Use a multi-stage degreasing furnace equipped with a thermogravimetric analyzer. Solvent degreasing: Use n-hexane as the solvent, temperature 50-70℃, soaking time 3-5h; thermal degreasing: heating rate 1℃ / min, from room temperature to 200℃, keep warm for 2 hours; heating again, rate 0.5℃ / min, from 200℃ to 350℃, keep warm for 4 hours; cooling: cool to room temperature at a rate of 0.5℃ / min. The combination of solvent degreasing and thermal degreasing is adopted, and the heating rate (1℃ / min and 0.5℃ / min) is precisely controlled to ensure the slow and uniform removal of organic matter, greatly reduce the risk of deformation during the degreasing process, and achieve a more uniform and safer degreasing process.

[0020] (8) Intelligent sintering: Adaptive sintering equipment equipped with a laser scanning measurement device was used, with a heating rate of 2-4°C / min from room temperature to 1000°C and a holding temperature of 1 hour; a heating rate of 1-3°C / min from 1000°C to 1550°C and a holding temperature of 2 hours; a temperature reduction rate of 0.5-1.5°C / min from 1550°C to 1200°C and then natural cooling to room temperature; the staged heating and controlled cooling strategy during the sintering process effectively balanced densification and grain growth, reduced thermal stress, effectively controlled deformation during the sintering process, and optimized the densification process.

[0021] Furthermore, in step (1), the drying temperature is 100-140° C. for 3-6 hours to reduce the moisture content to below 0.1%, and the powder is classified using an air flow classifier to ensure that the particle size distribution meets the requirements.

[0022] Furthermore, in step (2), the ultrasonic dispersion power is 400-600W, the frequency is 30-60kHz, and the time is 20-40min; and the drying is performed at 40-80°C for 3-6h.

[0023] Furthermore, in step (3), the ball-to-material ratio is 10:1, the ball milling medium is zirconia balls, the ball milling speed is 200-400 rpm, the ball milling time is 3-6 hours, and the rotation direction is changed every 20-40 minutes.

[0024] Furthermore, the vacuum degree of the vacuum mixing in step (4) is -0.09 MPa, the mixing temperature is 100-140° C., and the mixing time is 1-3 h.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. Gradient particle size distribution: The ratio of three particle sizes of alumina powder is designed to achieve the optimal packing density, which not only improves the green strength, but also significantly reduces the sintering shrinkage, thereby reducing the risk of deformation.

[0027] 2. Nano-enhancement system: The synergistic effect of nano-zirconia, graphene and carbon nanotubes forms a multi-scale, multifunctional reinforcement network. Nano-zirconia fills microscopic pores to improve density and strength; graphene provides two-dimensional plane reinforcement, improves thermal conductivity and reduces thermal stress; carbon nanotubes form a three-dimensional network structure to improve toughness and conductivity. This unique combination not only significantly improves the mechanical properties of the material, but also effectively reduces deformation during sintering by improving thermal conductivity and stress distribution.

[0028] 3. Organic system optimization: The composite binder system of polyethylene, polypropylene and paraffin wax is used to achieve good fluidity and controllable degreasing process. This combination can reduce stress accumulation during the degreasing process while ensuring injection molding performance, further reducing the risk of deformation.

[0029] 4. Dispersion-lubrication synergy: Through the dispersing effect of oleic acid and polyethylene glycol and the lubricating effect of stearic acid and zinc stearate, the uniform dispersion of powder and good mold release performance are achieved. This not only improves the uniformity of the green body, but also reduces the stress accumulation during the molding process, laying the foundation for the subsequent low deformation sintering.

[0030] 5. Introduce real-time monitoring and adaptive adjustment functions in key processes such as granulation, injection molding, degreasing and sintering. For example, adjust the injection speed according to the cavity pressure during injection molding, and adjust the temperature curve according to the shrinkage rate during sintering. This dynamic adjustment mechanism greatly improves the consistency and accuracy of the product. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] Unless otherwise specified, the raw materials, reagents or devices used in the following examples and comparative examples can be obtained from conventional commercial sources or by existing known methods.

[0033] The microstructure of the prepared nanocomposite precision ceramic injection molding material samples was observed using a scanning electron microscope (SEM); the phase composition of the nanocomposite precision ceramic injection molding material samples was analyzed using an X-ray diffractometer.

[0034] Example 1

[0035] The embodiment of the present invention provides a nano-composite precision ceramic injection molding material, the formula of which is as follows by weight percentage:

[0036] Gradient particle size alumina powder (0.5μm 28%, 1μm 22%, 2μm 18%): 68%

[0037] Nano-zirconia (50nm): 7%

[0038] Graphene: 0.4%

[0039] Carbon nanotubes: 0.3%

[0040] Organic binder (polyethylene 11%, polypropylene 9%, paraffin 2%): 22%

[0041] Dispersant: (oleic acid 0.75%, polyethylene glycol 0.75%) 1.5%

[0042] Lubricant: (stearic acid 0.3%, zinc stearate 0.5%) 0.8%

[0043] The embodiment of the present invention also provides a method for preparing a nano-composite precision ceramic injection molding material, comprising the following steps:

[0044] (1) Alumina powder pretreatment: Alumina powders of three particle sizes were dried at 120° C. for 4 hours to reduce the moisture content to below 0.1%, and the powders were classified using an air classifier.

[0045] (2) Dispersion of nanomaterials: Nano-zirconia, graphene and carbon nanotubes were added to anhydrous ethanol according to the formula ratio, and treated with an ultrasonic disperser at a power of 500 W and a frequency of 40 kHz for 30 minutes. The mixture was then vacuum filtered and dried at 60° C. for 4 hours.

[0046] (3) High-energy ball milling mixing: The powders of step (1) and step (2) are placed in a high-energy ball mill with a ball-to-material ratio of 10:1, zirconia balls as the ball milling medium, a ball milling speed of 300 rpm, a ball milling time of 4 hours, and the rotation direction is changed every 30 minutes to ensure uniform mixing.

[0047] (4) Vacuum mixing: Heat the organic binder to 120°C to melt it, add the mixed powder and the molten organic component into a vacuum mixer, vacuum degree -0.09 MPa, mixing temperature 120°C, then add the dispersant and lubricant, and mix for 2 hours.

[0048] (5) Intelligent granulation: Use an intelligent granulator with an online particle size analyzer, with an extrusion temperature of 115°C and a screw speed of 30 rpm. The cutting speed is automatically adjusted according to the real-time particle size distribution, with a target particle size range of 2-5 mm. The cooling temperature is controlled at 15-20°C to ensure that the particles have a regular shape.

[0049] (6) Intelligent injection molding: Intelligent injection molding machine is used, equipped with cavity pressure sensor and temperature sensor, and barrel temperature setting: 90℃ for feeding section, 105℃ for compression section, and 120℃ for metering section. Mold temperature is 40℃, and injection pressure is 80MPa. Injection speed is adjusted in real time according to cavity pressure to ensure uniform filling. Holding time is 15 seconds, and holding pressure is 60MPa.

[0050] (7) Multi-stage intelligent degreasing: Use a multi-stage degreasing furnace equipped with a thermogravimetric analyzer to monitor weight loss in real time:

[0051] a) First stage (solvent degreasing): using n-hexane as solvent, temperature 60°C, soaking time 4 hours.

[0052] b) Second stage (thermal degreasing): heating rate 1℃ / min, from room temperature to 200℃, keep at 200℃ for 2 hours; heating rate 0.5℃ / min, from 200℃ to 350℃, keep at 350℃ for 4 hours.

[0053] c) Cooling: Cool down to room temperature at a rate of 0.5°C / min.

[0054] (8) Adaptive sintering: An adaptive sintering system is used, equipped with a laser scanning measurement device, to monitor the size changes of the sample in real time.

[0055] a) Pre-sintering stage: heating rate 3 °C / min, from room temperature to 1000 °C, and keeping at 1000 °C for 1 hour to promote initial densification.

[0056] b) Main sintering stage:

[0057] The heating rate was 2°C / min, from 1000°C to 1550°C, and the temperature was kept at 1550°C for 2 hours.

[0058] c) Cooling stage:

[0059] The temperature was decreased from 1550°C to 1200°C at a rate of 1°C / min, and then naturally cooled from 1200°C to room temperature.

[0060] The samples were prepared into test bars with a size of 50 mm × 10 mm × 4 mm for testing.

[0061] Comparative Example 1

[0062] Comparative Example 1 of the present invention provides a ceramic injection molding material, the formula of which is as follows by weight percentage:

[0063] Single particle size alumina powder (1μm): 75%

[0064] Organic binder (polyethylene): 23%

[0065] Dispersant: (oleic acid 0.5%, polyethylene glycol 0.5%) 1%

[0066] Lubricant: (stearic acid 0.6%, zinc stearate 0.4%) 1%

[0067] Comparative Example 1 of the present invention also provides a method for preparing a ceramic injection molding material, comprising the following steps:

[0068] (1) Conventional ball milling: 200 rpm, 2 hours.

[0069] (2) Conventional mixing: 110°C, 1.5 hours.

[0070] (3) Conventional granulation: fixed cutting speed.

[0071] (4) Conventional injection molding: fixed injection parameters.

[0072] (5) Single thermal degreasing: 25-600℃, constant heating rate 2℃ / min.

[0073] (6) Conventional sintering: maximum temperature 1600°C, 2 hours, fixed sintering curve.

[0074] The samples were prepared into test bars with a size of 50 mm × 10 mm × 4 mm for testing. Test results:

[0075] The performance and microstructure of Example 1 and Comparative Example 1 were tested, and the results are shown in Table 1:

[0076] Table 1: Performance test results of ceramic injection molding materials of Example 1 and Comparative Example 1

[0077]

[0078]

[0079] Result analysis:

[0080] 1. Low deformation and shrinkage: The linear shrinkage (0.8%) and dimensional deformation (0.2%) of Example 1 are significantly lower than those of Comparative Example 1 (2.3%) and dimensional deformation (1.1%). This demonstrates the superiority of the gradient particle size distribution and nano-enhancement system of the present invention in controlling sintering deformation, and directly supports the innovation of the present invention in reducing sintering deformation. This feature is crucial for the production of high-precision semiconductor packaging components.

[0081] 2. High density: The relative density of Example 1 (99.5%) is higher than that of Comparative Example 1 (97.2%), indicating that the formula and process of the present invention can achieve better densification effect.

[0082] 3. Excellent mechanical properties: The flexural strength (480 MPa) and Vickers hardness (1950 HV) of Example 1 are significantly higher than those of Comparative Example 1 (350 MPa) and Vickers hardness (1680 HV), which demonstrates the synergistic reinforcement effect of nano-zirconia, graphene and carbon nanotubes.

[0083] 4. Improved thermal performance: Example 1 exhibits higher thermal conductivity (35 W / (m·K)) and better thermal shock resistance (95% strength retention), which is due to the addition of graphene and carbon nanotubes. The high thermal conductivity helps to evenly disperse heat and reduce thermal stress, thereby improving thermal shock resistance; the lower thermal expansion coefficient (7.2×10^-6 / ℃) also helps to reduce stress accumulation during thermal cycling.

[0084] 5. Oxidation resistance: Example 1 exhibits better oxidation resistance in the high temperature oxidation test (weight increase is only 0.05%), which may be due to the dense microstructure and the protective effect of the carbon nanomaterials.

[0085] 6. Electrical properties: The resistivity of Example 1 (10^12Ω·cm) is lower than that of Comparative Example 1 (10^15Ω·cm), but still within the range of insulating materials. This moderate conductivity may help dissipate static charges and reduce static electricity problems during processing.

[0086] 7. Microstructure: SEM observation shows that the grain size of Example 1 is smaller and more evenly distributed. This is because the addition of nano-zirconia and carbon nanomaterials inhibits grain growth, which is beneficial to improving the strength and toughness of the material. The network-like carbon nanotube structure may play an important role in strengthening the material and improving thermal conductivity.

[0087] 8. Crystallinity and phase composition: XRD analysis shows that Example 1 has a higher crystallinity, which may be one of the reasons for its superior mechanical properties. The presence of a small amount of t-ZrO2 phase may further improve the toughness of the material through a phase transformation toughening mechanism.

[0088] In summary, the ceramic injection molding compound prepared in Example 1 not only reduces deformation, but also achieves performance improvement in multiple aspects such as strength, hardness, thermal conductivity, thermal shock resistance, etc. This comprehensive performance improvement enables the ceramic injection molding compound of the present invention to have a wider application prospect in the field of semiconductor packaging.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A nano-composite precision ceramic injection molding material, characterized in that: The invention comprises the following components in weight percentage: 65-70% alumina powder, 5-8% nano zirconium oxide, 0.3-0.5% graphene, 0.2-0.4% carbon nanotube, 20-25% organic binder, 1-2% dispersant and 0.5-1% lubricant; the alumina powder is composed of alumina powders of three particle sizes.

2. The nanocomposite precision ceramic injection molding material according to claim 1, characterized in that: In terms of mass fraction, the three types of alumina powders are composed of 0.5 μm (D50) alumina powder, 1 μm (D50) alumina powder and 2 μm (D50) alumina powder in a mass ratio of (5-6): (4-5): (3-4). Further, the organic binder is composed of polyethylene, polypropylene and paraffin in a mass ratio of (5-6): (4-5): (1-1.5).

3. The nanocomposite precision ceramic injection molding material according to claim 1, characterized in that: Calculated by mass fraction, the organic binder is composed of polyethylene, polypropylene and paraffin in a mass ratio of (5-6):(4-5):(1-1.5).

4. The nanocomposite precision ceramic injection molding material according to claim 1, characterized in that: Calculated by mass fraction, the dispersant consists of oleic acid and polyethylene glycol in a mass ratio of 1:

1.

5. The nanocomposite precision ceramic injection molding material according to claim 1, characterized in that: Calculated by mass fraction, the lubricant consists of stearic acid and zinc stearate in a mass ratio of (3-5):(2-5).

6. The method for preparing the nanocomposite precision ceramic injection molding material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Alumina powder pretreatment: drying alumina powders of three particle sizes and grading the powders; (2) Nanomaterial dispersion: adding nano zirconium oxide, graphene and carbon nanotubes into anhydrous ethanol according to the ratio of claim 1, performing ultrasonic dispersion treatment and drying; (3) powder mixing: placing the powders of step (1) and step (2) in a ball mill for ball milling to obtain mixed powders; (4) Mixing: heating the organic binder until it is melted, adding the powder mixed in step (3) and the melted organic binder into a mixing device, and then adding a dispersant and a lubricant, and performing vacuum mixing; (5) Intelligent granulation: Use intelligent granulation equipment with an online particle size analyzer, extrusion temperature 100-120°C, screw speed 20-40rpm, target particle size 2-5mm, cooling temperature 15-20°C; (6) Injection molding: Use intelligent injection molding equipment equipped with cavity pressure sensor and temperature sensor, barrel temperature: feeding section 85-95°C, compression section 100-110°C, metering section 110-130°C; mold temperature 35-45°C, injection pressure 70-90MPa; holding time 10-20 seconds, holding pressure 50-70MPa; (7) Intelligent degreasing: using a multi-stage degreasing furnace equipped with a thermogravimetric analyzer, solvent degreasing: using n-hexane as the solvent, the temperature is 50-70°C, and the soaking time is 3-5h; thermal degreasing: heating rate is 1°C / min, from room temperature to 200°C, and keep warm for 2 hours; heating again, the rate is 0.5°C / min, from 200°C to 350°C, and keep warm for 4 hours; Cooling: cool to room temperature at a rate of 0.5°C / min; (8) Intelligent sintering: Use an adaptive sintering device equipped with a laser scanning measurement device, with a heating rate of 2-4°C / min from room temperature to 1000°C and a heat preservation period of 1 hour; a heating rate of 1-3°C / min from 1000°C to 1550°C and a heat preservation period of 2 hours; a cooling rate of 0.5-1.5°C / min from 1550°C to 1200°C and then natural cooling to room temperature.

7. The method for preparing the nanocomposite precision ceramic injection molding material according to claim 6, characterized in that: The drying temperature in step (1) is 100-140° C. for 3-6 hours.

8. The method for preparing the nanocomposite precision ceramic injection molding material according to claim 6, characterized in that: In the step (2), the ultrasonic dispersion power is 400-600W, the frequency is 30-60kHz, and the time is 20-40min; and the drying is carried out at 40-80°C for 3-6h.

9. The method for preparing the nanocomposite precision ceramic injection molding material according to claim 6, characterized in that: In the step (3), the ball-to-material ratio is 10:1, the ball milling medium is zirconia balls, the ball milling speed is 200-400 rpm, the ball milling time is 3-6 hours, and the rotation direction is changed every 20-40 minutes.

10. The method for preparing the nanocomposite precision ceramic injection molding material according to claim 6, characterized in that: The vacuum degree of the vacuum mixing in step (4) is -0.09 MPa, the mixing temperature is 100-140° C., and the mixing time is 1-3 h.

Citation Information

Patent Citations

  • Preparation method of graphene / carbon nano tubes reinforced aluminum oxide ceramic coating

    CN106946551A

  • Carbon nano tube and graphene synergistically reinforced aluminum oxide-based composite material and preparation method thereof

    CN111410517A

  • Feed for aluminum oxide injection molding, aluminum oxide ceramic and preparation method

    CN113698185A

  • ZTA ceramic powder catalytic degreasing type injection feed for large-size thick-wall injection molding and preparation method of ZTA ceramic powder catalytic degreasing type injection feed

    CN115353371A

  • Preparation method of composite active ceramic

    CN116639991A

Cited By

  • High-density ZTA ceramic and preparation method thereof

    CN119954500A

  • High-density zta ceramic and preparation method thereof

    CN119954500B